Combat Memoirs of the Vietnam War (Via Litterae (ISSN 2176-6800): Revista de Linguística e Teoria Literária, 2013)
This article addresses the combat memoirs of the Vietnam War, autobiographical narratives written after the fact by soldier-writers, with an emphasis on their first-hand experiences of battle and their accompanying emotions. After an introduction that discusses the motivations, truth claims, and narrative structures of such works, two well-known examples (both were best-sellers on their publication) are examined at length:  Ron Kovic’s Born on the Fourth of July (1976), and Philip Caputo’s Rumors of War (1977). While both works follow the familiar trajectory of before-during-after, in which the cultural influences that made them both want to go to war and the consequences, physical and emotional of having survived it, they differ in the different socio-economic background of the authors and consequent attitudes toward their experience, as well as how the war has determined their later lives.